Correlation Between Stress, Immunity and Intestinal Microbiota - Оxana N. Komarova; Anatoly I. Khavkin (Педиатрическая фармакология)
Recent studies have shown the correlation between stress, immunity and intestinal microbiota. Chronic stress is associated with high production of inflammation mediators and risk of infection development, chronic systemic inflammation and inflammatory diseases development, as well as depressive disorders. Intestinal microbiota produces a wide range of compounds important for the organism: all major neurotransmitters, including serotonin, cytokines, tryptophan and short-chain fatty acids. Serotonin deficiency is considered as significant cause factor for development of anxiety, aggression, affective disorders and stress. Tryptophan is the serotonin precursor. Tryptophan is produced by intestinal microbiota or derived from food can be metabolized into kinurenine. Proinflammatory cytokines activate hypothalamus-pituitary-adrenal axis that increases of the level of circulating kinurenine and reduces the serotonin synthesis. Besides that, more kinurenine enters the brain during the inflammation process, and the neurotoxic pathway of kinurenine metabolism overwhelm the neuroprotective one. The less various microbiota microbiota is associated with increased response of the hypothalamus-pituitary-adrenal system, increase of pro-inflammatory cytokines, reduction of stress resistance, and depression. Enrichment of the diet with prebiotic components increases the diversity of the intestinal microbiota. Dietary interventions for intestinal microbiome also include probiotics promoting increased body resistance and cause less exposure to depression.